European Perspectives of Hospital Pharmacy - Changing Roles and Workforce Challenges - Sule, Andras (Arhiv za farmaciju, 2022)
The traditional role of hospital pharmacists that concentrated mainly on dispensing and compounding has evolved over the last decades. In addition to these fundamental tasks, other equally important ones, such as performing quality controls, providing relevant expertise concerning pharmaceutical products and medical devices, procurement, engagement in clinical trials and carrying out clinical pharmacy services were added to the scope of hospital pharmacy activities. Recently, partially because of the Covid-19 pandemic, a newfound convergence became obvious about the trends in which direction European healthcare systems progressed. Bedside clinical pharmacy services with their focus on patient education, medicines reconciliation, participation in vaccination programs and engagement in multidisciplinary treatment teams have become an important feature of the ‘post-pandemic’ hospital pharmacy practice in Europe. Pharmacists in clinical roles should play a leading part in evidence-based therapeutic decision-making, developing individual treatment plans, as well as in direct patient counselling activities for vulnerable patient populations. The emergence of these novel activities not only bring about significant responsibilities, but challenges for human resources development as well. Comprehensive action plans are needed involving healthcare providers, professional societies and pharmacy schools to formulate a coordinated roadmap that enables pharmacy professionals becoming available in sufficient numbers and competencies for employment in novel hospital and clinical pharmacy functions.In this session, participants will be shown prospective solutions to foster the changing roles of hospital pharmacy in a systematic manner, considering numerous policy activities, education, reimbursement strategies, human resource planning and well-defined competencies. Development directions for pharmacy curricula will also be presented.